Mapping Journalism Cultures Across Nations: A Comparative Study of 18 Countries - Mellado-Ruiz, C (2011)
This article reports key findings from a comparative survey of the role perceptions, epistemological orientations and ethical views of 1800 journalists from 18 countries. The results show that detachment, non-involvement, providing political information and monitoring the government are considered essential journalistic functions around the globe. Impartiality, the reliability and factualness of information, as well as adherence to universal ethical principles are also valued worldwide, though their perceived importance varies across countries. Various aspects of interventionism, objectivism and the importance of separating facts from opinion, on the other hand, seem to play out differently around the globe. Western journalists are generally less supportive of any active promotion of particular values, ideas and social change, and they adhere more to universal principles in their ethical decisions. Journalists from non-western contexts, on the other hand, tend to be more interventionist in their role perceptions and more flexible in their ethical views. © 2011 Taylor & Francis.